2008
DOI: 10.1186/1471-230x-8-59
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in culture positive and culture negative ascitic fluid infection in patients with viral cirrhosis: cohort study

Abstract: Background: Ascitic fluid infection (AFI) in cirrhotic patients has a high morbidity and mortality. It has two variants namely, spontaneous bacterial peritonitis (SBP) and culture negative neutrocytic ascites (CNNA). The aim of this study was to determine the outcome in cirrhotic patients with culture positive (SBP) and culture negative neutrocytic ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
39
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 18 publications
10
39
1
4
Order By: Relevance
“…The incidence of SBP (including CNNA and BA) was found to be 25% in our cohort. International studies reports an incidence of 8 -30% in CLD patients with ascites, 3,14 which reciprocates that our results are in concordance with these reports. Regarding SBP variants, CNNA was the most common followed by Bacterascites and classical SBP in descending order.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The incidence of SBP (including CNNA and BA) was found to be 25% in our cohort. International studies reports an incidence of 8 -30% in CLD patients with ascites, 3,14 which reciprocates that our results are in concordance with these reports. Regarding SBP variants, CNNA was the most common followed by Bacterascites and classical SBP in descending order.…”
Section: Discussionsupporting
confidence: 83%
“…International literature suggests a culture positivity rate of 31 -71%. 14,22 A study from Lahore showed similar results (47.5%) 16 but some studies have reported less than 25% rates of culture positivity. 14,23 This difference may be due to the different culture techniques as reported by Pawar et al showing varied rate for different technique.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Fernandez J, et al [2] had shown 25% SBP among patients with cirrhosis of liver. Earlier published local studies on AFI showed frequency of SBP to be (23.5%) and (38.23%) respectively with similar microbiological spectrum [35] [36]. The low frequency of SBP in above studies is probably due to smaller sample size.…”
Section: Discussionmentioning
confidence: 55%
“…69.93% patients among AFI had CNNA in this study. Above mentioned studies had (76.4%) and (57.84%) CNNA [35] [36].…”
Section: Discussionmentioning
confidence: 99%